A percutaneous treatment strategy of an adult patient with a bicuspid aortic valve, coarctation of the aorta, and an exceptionally large aneurysm of a collateral artery: Case report and literature overview - Verheijen, D. B. H.; Stöger, J. Lauran; van der Kley, F.; Schalij, M. J.; Jongbloed, M. R. M.; Vliegen, H. W.; Kiès, P.; Egorova, A. D. (Frontiers in Cardiovascular Medicine, 2022)
Coarctation of the aorta(CoA) is a congenital heart defect that is associated with a bicuspid aortic valve (BAV), ascending aorta dilatation, intracerebral aneurysms and premature atherosclerotic disease. First presentation during late adulthood is rare and is frequently driven by late sequala. Hypertrophic collateral arteries can develop aneurysms which are at risk for spontaneous rupture, however, treatment recommendations for these aneurysms are scarce. Here, we describe the clinical course and percutaneous treatment strategy of a patient with late diagnosis of a pin-point CoA, a BAV with moderate regurgitation and an exceptionally large aneurysm of a collateral artery. A 59 year old female was diagnosed with a Streptococcus Bovis endocarditis of a BAV with moderate aortic valve regurgitation and a small vegetation(< 5mm) on the non-coronary cusp. Work-up revealed hypertension and an adenocarcinoma in situ of the ascending colon, considered the bacteremia porte d'entrée, for which a curative hemicolectomy was performed. Echocardiography showed a narrowing of the aorta distal from the origin of the left subclavian artery with antegrade diastolic flow with a pathognomonic “sawtooth” pattern and an estimated pressure gradient of >70mmHg. Computed tomography angiography (CTA) showed a network of well-developed collateral arteries and a levoatriocardinal vein. One of the collateral arteries arising from the left subclavian artery revealed an exceptionally large aneurysmatic dilation (29x24x24mm). Invasive assessment confirmed a hemodynamically significant CoA. Treatment involved balloon dilatation and placement of a covered stent at the site of the pin-point CoA and a percutaneous coronary intervention (PCI) of the stenosis in the left anterior descending artery. No residual gradient over the CoA was observed. Antihypertensive drugs could be discontinued and CTA performed 4 months later showed regression and thrombosis of the numerous collaterals and, importantly, thrombosis of the large aneurysm. This case illustrates late diagnosis of CoA with associated congenital heart defects and late sequelae including hypertension, BAV endocarditis, coronary artery disease, and aneurysm formation of the extensive collateral network. The patient underwent pharmacological and percutaneous treatment ultimately resulting in alleviation of the CoA, normalization of the blood pressure, reduction of collateral flow and thrombosis of the large aneurysm of the collateral artery.